Training on Processing Plastic Waste into Creative Products for PKK Mothers in Tambak Oso Village Sidoarjo - Agustin, Dyan; Djuni, Erwin; Brahmantio, Athilla; Dahlan, Ahmad (Nusantara Science and Technology Proceedings, 2020)
Tambak Oso Village is a densely populated village on the coast. Every day a lot of waste is generated, both household waste and waste from the embankment. The accumulation of garbage is a serious problem for Tambak Oso village, some residents even dump trash in the river. The collected waste is currently not being processed, the only way is just to burn them, which of course creates an odor and disturbs health, especially plastic waste. Therefore, training efforts are needed to process plastic waste into creative products, including accessories (bags, flower vases, flowers) and interior products (lampshades and furniture from used bottles / eco-bricks). By processing plastic waste into creative products, the problem of plastic waste can be overcome. Human resources that are suitable for this activity are PKK mothers (program at the village level to educate women on various aspects of family welfare). They will be trained in the plastic waste processing process so that they will generate new skills and business opportunities. The results obtained after the training were the knowledge of PKK mothers, especially on making chairs from used bottles (eco-bricks). With eco-bricks, they can reduce a lot of plastic waste. Besides, a garbage bank has also been formed to make it easier for mothers to help with plastic waste so that it can increasing the income of PKK mothers in Tambak Oso Village.